Pengujian Karakteristik Tanah pada Daerah Ngasem Kediri Sebagai Dasar Perencanaan Konstruksi - Rahmat Heru Supriyo; Agata Iwan Candra; Fransesco Indra Permana; Fidyan Mamlu'atul Husna; Afriyan Arsya Sabilla; Zaizafun Zakiya (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2023)
Ngasem District, Kediri Regency is an area that is close to educational centers, shopping centers, and tourism areas, so it is suitable to build housing in the area. However, there were several residents' houses that were damaged, such as cracked floors and walls. One of the contributing factors is the condition of the soil. This study aims to conduct a soil investigation to determine the characteristics of the soil in the area by using laboratory tests including sieving gradation tests, atterberg limits, compaction and soil shear strength and the results show that the soil in the area is classified as SW-SC soil, namely well graded sand with a little clay mixture so it has low plasticity. In addition, the maximum dry unit weight was 1.76 gr/cm3, the optimum moisture content was 15.38% from the compaction test and the cohesion value was 0.894 kPa and the shear angle was 29.685° from the shear strength test. The results of this study can be useful in providing an overview of soil characteristics as a reference in construction projects.Keywords: soil characteristics, SW-SC soil, atterberg boundaries, Ngasem District